Design optimization of high performance tapping mode AFM probe - Li, Zhenhua; Shi, Tielin; Xia, Qi (Microsystem technologies : sensors, actuators, systems integration, 2018)
To enhance the measurement performance of tapping-mode atomic force microscopy (TM-AFM), it is highly desirable that the TM-AFM probe has high resonant frequency and large effective slope at its free end. However, the two design objectives may lead to conflict requirements on the geometry of probe. Conventional design approaches that involve a lot of trials and errors are not so effective to solve such a complex design problem. Therefore, in order to address this difficulty, a structural optimization problem is formulated. The objective of optimization is to ensure the mode shape of probe match a user-specified target shape and the corresponding resonant frequency is maximized. Similarity between the actual mode shape and the target is characterized by modal assurance criterion. Users can freely select which vibration mode is to be optimized. A three-layer geometry model is used to represent cantilever probes. The middle layer is not subject to optimization. The top and bottom layers have the same width profile, and it is iteratively changed during the optimization. The optimization problem is solved through a gradient based method. Examples of design optimization show that the proposed method is effective.